A new species of Bryoleuca Hampson, 1908 from Afghanistan (Lepidoptera, Noctuidae, Bryophilinae) - Pekarsky, Oleg (Zootaxa, 2015)
A new species of the raptricula species-group, Bryoleuca pljushtchi sp. n. is described. A diagnostic comparison is made with Bryoleuca raptricula ([Denis & Schiffermüller], 1775), Bryoleuca felina (Eversmann, 1852), Bryoleuca orthogramma (Boursin, 1954), Bryoleuca volodia An, Choi & Ronkay, 2013 and Bryoleuca nahnybidai Pekarsky, 2014. Adults and female genitalia of the new species and its closest relatives are illustrated. Modern taxonomic studies of the raptricula-group started by Fibiger et al. (2009) and got progress by the clarification of the taxonomic status of B. felina (Pekarsky & Ronkay 2010). Subsequently, further two newly recognised species were described in the last two years, B. volodia and B. nahnybidai. The first attempt to prepare the checklist of the subfamily was made by Hacker (1990) and, later, European check list was given in the Noctuidae Europaeae, Vol. 11 (Fibiger et al. 2009). As for the fauna of Afghanistan, Koçak and Kemal (2012) listed twelve Bryophilinae species one of which, B. raptricula, belongs to the genus Bryoleuca. The taxonomic situation of the raptricula species-complex is far not completely known yet. Present paper contains the description of a new Bryoleuca species from Afghanistan. The single female of this new species was collected by Ukrainian entomologists Igor Pljushtch and Oleg Pak in Central Afghanistan in 2013.